An Improved Software Project Monitoring Task Model of Agile Kanban Method: A Practitioners’ Perspective - Omar, Mazni; Alaidaros, Hamzah; Romli, Rohaida (2020)
Monitoring software project development is essential to ensure that the project progress is according to budget, schedule, and quality expectations. Currently, Agile Methods (AMs) have received wide recognition within the software engineering (SE) field due to their flexibility and effectiveness. One of the AMs methods used in managing software project development is Kanban method. This method is gaining attention due to its ability to enhance understanding, visibility, and controlling the project workflow. Thus, this paper aims to discuss the initial result of the proposed model for improving the software project monitoring task of the Agile Kanban method (i-KAM). To achieve this aim, the expert review method was used to ensure that suitable components and associated criteria have been included in i-KAM. In this study, six domain experts, which are software practitioners, have been identified based on predefined characteristics. The proposed model was verified based on five dimensions, which are understandability, relevance, feasibility, organization, and comprehensiveness. The experts’ opinions and comments were obtained and subsequently quantified by using descriptive analysis. Findings revealed that this study has fulfilled its objective and has acquired constructive suggestions from the practitioners’ perspective. Future work will continue to enhance i-KAM according to the recommendations and remarks from the experts. A focus group and case study methods could be conducted in order to validate the revised i-KAM. Besides, a prototype will be developed and then implemented within a real software development setting.